Gradientes espaciais no reservatório de Foz do Areia - Rio Iguaçu - Frana, Vitor André (2011)
Spatial gradients in aquatic environments reflect gradual changes in physical, chemical and biological features along of the longitudinal, transverse and vertical axis, which are of relevance for understanding the mechanisms that operate in reservoirs. This work aims to verify if assemblage abundance of fish of Foz do Areia reservoir presents distinct longitudinal gradients, forming fluvial, transitional and lacustrine zones, and if this assemblage is differentiated in bottom, surface and margin regions. It was also valuated the longitudinal gradients formation in physical and chemical variables in surface and if these variables present concordance with assemblage abundance. For this, fish samples were collected quarterly between January 2004 and October 2007, in bottom, surface and margin regions, in three zones, near the dam (LAC), transition (TRA) and up-stream (FLU). The abundances were expressed as catch per unit effort (CPUE), summarized by Detrended Correspondence Analysis (DCA) and spatially compared with the Multi-Response Permutation Procedure (MRPP). Additionally, the indicator species analysis (indval) was performed aims to elucidate preferential zone and regions of each species. The degree of congruence between the physical and chemical water variables and assemblage fish matrices in surface was evaluated with Protest after summarized them with Nonmetric Multidimensional Scaling (NMS). Therefore, it was verified that assemblage structure distinguished for the zone (LAC, TRA and FLU), and more sharply between in bottom, surface and margin regions. Additionally, it was identified that there was longitudinal gradient of fishes assemblage abundance, and it gradient was different in bottom, surface and margin. Furthermore, the longitudinal gradients of physical and chemical variables were observed and they were consistent with the fish assemblage structure in surface. Thus, the Foz de Areia reservoir had spatial gradients, both, in the fish’s assemblage and in the physical and chemical variables, which are concordant. Moreover, dependencies between the longitudinal axis, vertical and horizontal were evident in assemblage.